Rede urbana e produção do território: complementaridades, competitividades e sinergias entre Barreiras e Luís Eduardo Magalhães - Santos, Iann Dellano da Silva (2021)
Taking the complexity attached to the urban network’s hierarchy in the West Region of Bahia into consideration, and also the current context of socio-spatial formation in the region, it becomes pertinent to understand the mechanisms sustained by relationships of complementarities, competitivities and synergies between the main cities of the regional urban network: Barreiras and Luís Eduardo Magalhães. In order to promote this comprehension, it's necessary to discuss the network's concept, keeping in mind that urban network is a concept which comes from its addition to the territories' production, so then we can see the urban network as a material construction deriving from its own territories' production; to conceive the existence of complementary, competitive and synergistic relationships between urban centers in a given urban network and how these relationships happen in the globalized geographical space; to know the urban network in Bahia’s West, joining periods of formation, structuring and restructuring of the urban network in this region of Bahia; and also to analyze the complementarity relationship between Barreiras and Luís Eduardo Magalhães, represented by elements of political, social, economic and urban nature, and the competitive relationship between the same centers, showing their respective importance in the field of agricultural production, based on elements of economic and geographical nature, including a third synergistic movement present in these relationships. To achieve these goals, a bibliographical and documentary research is carried out with a qualitative approach that unfolds in five chapters, including an explanatory note in which the thesis is defended, considering the coexistence of relations: complementarity, competitiveness and synergy; which gives meaning for the urban network in Bahia’s West. Because of their complementarity, Barreiras and Luís Eduardo Magalhães became urban centers that control the regional urban network, with emphasis on Barreiras because of the localized services and its influence on the urban net. On the other hand, when it comes to competitiveness Barreiras and Luís Eduardo Magalhães are in tune for the logic of reproduction, however Luís Eduardo Magalhães is more important for satisfying this reproduction too much. In this way, synergy is between complementarity and competitiveness and is also related to the dynamics and functioning of the urban network in Bahia’s West.